A Critical Incident Technique Study of the Facilitation of Gang Entry: Perspectives of Indigenous Men Ex-Gang Members. Issue 5 (27th May 2016) - Goodwill, Alanaise
ABSTRACT: The aim of the study was to describe incidents that facilitated gang entry among 10 Indigenous men who survived and exited from gang life in Canada's Prairies. The critical incident technique was applied as participants responded to this question: What facilitated gang entry for you? A total of 103 incidents that facilitated gang entry for participants were sorted into 13 distinct categories. These events led to a progression of gang activity where the gang lifestyle provided validation, provided a site for dedication and learning, and generated traumatic consequences for participants' actions. Qualitative textual data vignettes, counseling, and research recommendations are provided.